Literature, principle and the basics of network value creation in R&D: the relationship with economy - Ale Ebrahim, N.; Ahmed, S.; Taha , Z. (2008)
The internationalization of R&D network is a recent phenomenon. In this knowledgebased environment, the driving forces for this phenomenon are digitization, the internet, and high-speed data networks that are keys to address many of the operational issues from design to logistics and distribution. From the other direction to surviving in the highly competitive industry, requires strategies to collaborate with or compete with suitable firms within a network in the New Product Development process. The growing internationalization of R&D activities challenges multinational corporations (MNCs) to formulate technology strategies and manage increasingly diffuse and diverse networks of R&D laboratories and alliances in the context of disparate national institutions. Research and development functions are fundamental drivers of value creation in technology-based enterprises. Successful R&D is a function of invention and R&D network. This paper studies R&D network issues from the perspective of their impact on value creation. It is observed that most of the research activities encourage and support R&D networks and influences in economic development.